School Library Management in Improving Students' Science Literacy Skills - Zurhidayati, Zurhidayati; Imamora, Marjoni; Jamilus, Jamilus (LPPM Institut Pendidikan Nusantara Global, 2025)
The problem in this study is the still minimal collection of science, fiction and non-fiction books that can support students' science skills, so that students do not experience a significant spike in borrowing books and visiting the library at SMPN 7 Sijunjung. This study uses a qualitative method with research informants consisting of the principal, head of the library, librarian, teacher, and students with data collection techniques in the form of observation, interviews and documentation studies. Data analysis uses data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate: (1) The management planning of the SMPN 7 Sijunjung library to improve students' science literacy skills has been planned very well because the library has conducted an analysis of needs before designing and establishing a program and improving literature collections, library facilities, planning guidance and training, conducting collaboration, and program evaluation. (2) The implementation of library management at SMPN 7 Sijunjung to improve students' science literacy skills has been carried out very well, namely by providing and updating science literacy collections, organizing science literacy programs, providing science literacy training and guidance, providing science literacy support facilities, collaborating with teachers and the science community and conducting program evaluations. (3) Evaluation of library management at SMPN 7 Sijunjung to improve students' science literacy skills has been carried out by conducting evaluations of library programs, library users and through the use of evaluation tools and techniques.